Patients with Primary Immunodeficiencies Are a Reservoir of Poliovirus and a Risk to Polio Eradication - Aghamohammadi, Asghar; Abolhassani, Hassan; Kutukculer, Necil; Wassilak, Steve G.; Pallansch, Mark A.; Kluglein, Samantha; Quinn, Jessica; Sutter, Roland W.; Wang, Xiaochuan; Sanal, Ozden; Latysheva, Tatiana; Ikinciogullari, Aydan; et al. (Frontiers in Immunology, 2017)
Immunodeficiency-associated vaccine-derived polioviruses (iVDPVs) have been isolated from primary immunodeficiency (PID) patients exposed to oral poliovirus vaccine (OPV). Patients may excrete poliovirus strains for months or years; the excreted viruses are frequently highly divergent from the parental OPV and have been shown to be as neurovirulent as wild virus. Thus, these patients represent a potential reservoir for transmission of neurovirulent polioviruses in the post-eradication era. In support of WHO recommendations to better estimate the prevalence of poliovirus excreters among PIDs and characterize genetic evolution of these strains, 635 patients including 570 with primary antibody deficiencies and 65 combined immunodeficiencies were studied from 13 OPV-using countries. Two stool samples were collected over 4 days, tested for enterovirus, and the poliovirus positive samples were sequenced. Thirteen patients (2%) excreted polioviruses, most for less than 2 months following identification of infection. Five (0.8%) were classified as iVDPVs (only in combined immunodeficiencies and mostly poliovirus serotype 2). Non-polio enteroviruses were detected in 30 patients (4.7%). Patients with combined immunodeficiencies had increased risk of delayed poliovirus clearance compared to primary antibody deficiencies. Usually, iVDPV was detected in subjects with combined immunodeficiencies in a short period of time after OPV exposure, most for less than 6 months. Surveillance for poliovirus excretion among PID patients should be reinforced until polio eradication is certified and the use of OPV is stopped. Survival rates among PID patients are improving in lower- and middle-income countries and iVDPV excreters are identified more frequently. Antivirals or enhanced immunotherapies presently in development represent the only potential means to manage the treatment of prolonged excreters and the risk they present to the polio endgame. Keywords: Poliovirus eradication, Immunodeficiency-associated vaccine-derived polioviruses, Oral poliovirus vaccine, Humoral immunodeficiency, Combined immunodeficiency, Primary immunodeficiency.